Surface rupture during the 6th of February 2023 Mw 7.6 Elbistan-Ekinözü (Kahramanmaraş) earthquake: implications for fault rupture dynamics along the northern branch of East Anatolian Fault Zone - Softa, Mustafa; Kocbulut, Fikret; Akgun, Elif; Aksoy, Ercan; Sozbilir, Hasan; Tatar, Orhan; Arslan, Gokhan (Tubitak Scientific & Technological Research Council Turkey, 2024)
On the 6th of February 2023, Mw 7.7 Pazarcik (Kahramanmaras) and Mw 7.6 Ekinozu (Kahramanmaras) earthquakes that occurred in Turkiye are devastating earthquake series that filled the existing seismic gaps on East Anatolian Fault Zone on the same day. The first Mw 7.7 earthquake caught most people in their sleep and 9 h later, a second one was triggered, ending up with more than 50k death toll, widespread damage to buildings, and massive landslides. This study presents the surface rupture geometry and coseismic displacement characteristics determined with field observations immediately after February 6, 2023, Ekinozu (Kahramanmaras, Turkiye) earthquake (Mw 7.6). Preliminary implications show that the total rupture length is 130 +/- 10 km on the cardak segment and Dogansehir segment, known as the northern branch of the East Anatolian Fault Zone. Left lateral strike-slip faulting is developed with a maximum horizontal displacement of 6.60 m and an average displacement of 3.00 m. Furthermore, the pitches of slip lines ranging from 0 degrees to 10 degrees were measured on the neoformed fault planes. In addition to that, surface rupture exhibits restraining bends and releasing bends structure at small scales on the cardak segment. From this point on, our preliminary results signify that cardak and Dogansehir segments were consecutively broken in Mw 7.6 Ekinozu (Kahramanmaras) earthquake that traced between Goksun and Nurhak region and from there reached the Eskikoy regions. Furthermore, potential stress may be concentrated on not only the Surgu segment which is on the transfer fault between the northern branch and the southern branch of East Anatolian Fault Zone but also the west of the cardak segment and the northeast of the Dogansehir segment near Yesilyurt (Malatya).
Keywords: East Anatolian Fault Zone; Ekinozu (Kahramanmaras) earthquake; cardak Segment; Dogansehir segment; surface rupture